Well Performance Following Matrix Acidizing Treatment: Case Study of the Mi4 Unit in Ahdeb Oil Field - ALAMEEDY, Usama; Al-Haleem, Ayad A.; Almalichy, Abdulameer (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
The productivity of oil wells may be improved by determining the value of enhancing well productivity and the likely reasons or sources of formation damage after the well has been recognized as underperforming. Oil well productivity may be improved, but the economics of this gradual improvement may be compromised. It is important to analyze the influence of the skin effect on the recovery of the reserve.   The acid treatment evaluated for the well AD-12, primarily for the zone Mi4;  using a license of Stimpro Stimulation Software to validate the experimental work to the field scale, this software is considered the most comprehensive instrument for planning and monitoring matrix acid treatments and utilizing actual data to provide a far better knowledge of the well's reaction, with methods that represent the reality of what is happening in the reservoir before, during, and after matrix acid treatments, through the post-treatment skin factor, which is the most frequently utilized statistic for analyzing stimulation treatments and relies on the geometry of the wormholed zone. Referring to the previous buildup tests for Ad-12, the skin value of -3.97 is approximately identical to or slightly larger than the skin value estimated by the acid treatment simulation using Stimpro. Moreover, when the simulator was performed, the invading fluid revealed two distinct depths of investigation inside the treated zone. While the fluid invasion in the bottom area has invaded deeply at a distance of 95 inches despite the top layer wormhole penetrating to a depth of 32 inches.